2013
DOI: 10.1063/1.4791786
|View full text |Cite
|
Sign up to set email alerts
|

An efficient non-Lambertian organic light-emitting diode using imprinted submicron-size zinc oxide pillar arrays

Abstract: We report phosphorescent organic light-emitting diodes with a substantially improved light outcoupling efficiency and a wider angular distribution through applying a layer of zinc oxide periodic nanopillar arrays by pattern replication in non-wetting templates technique. The devices exhibited the peak emission intensity at an emission angle of 40° compared to 0° for reference device using bare ITO-glass. The best device showed a peak luminance efficiency of 95.5 ± 1.5 cd/A at 0° emission (external quantum effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Based on these results, and combined with its transparency over the visible region as well as the ability to be grown into a variety of nanostructures, it is hoped that the ZnO NRA can be further tailored to improve the out-coupling of light from the emissive organic layers [50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, and combined with its transparency over the visible region as well as the ability to be grown into a variety of nanostructures, it is hoped that the ZnO NRA can be further tailored to improve the out-coupling of light from the emissive organic layers [50][51][52] .…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously demonstrated that photonic crystal nanostructures can be used above the glass surface for enhancing the LEE of an OLED device where the trapped light within the QLED escapes into the air as a result of Bragg diffraction and scattering from the nanostructures on the glass surface . Among them, ZnO nanostructures are promising materials as light outcoupling medium because of their high index and excellent optical transparency as well as easy solution fabrication process . For our case, the light extraction enhancement in QLEDs is investigated by placing ordered ZnO nanopillar arrays onto the glass surface of ITO‐glass substrates, as shown in Figure a.…”
Section: Resultsmentioning
confidence: 99%
“…The ITO/ organic mode has been out-coupled by a hexagonalclose-packed array [5], and ultra-low-index grid [6]. Additionally, the substrate mode has been extracted using microlens arrays [7,8] and zinc oxide pillar arrays [9].…”
mentioning
confidence: 99%